2013
DOI: 10.1515/hsz-2012-0302
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B1 receptor gene ablation affects hypothalamic CART productionb

Abstract: Abstract:A role for the kinin B1 receptor in energy-homeostatic processes was implicated in previous studies; notably, the studies where kinin B1 receptor knockout mice (B1 -/-) were shown to have impaired adiposity, impaired leptin and insulin production, lower feed efficiency, protection from liver steatosis and diet-induced obesity when fed a high fat diet (HFD). In particular, in a model where the B1 receptor is expressed exclusively in the adipose tissue, it rescues the plasma insulin concentration and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Recently, our group found that CART mRNA expression is elevated in the lateral hypothalamic area of B1KO mice. 24 Even though B1KO and B1B2KO mice show similarities in some aspects of metabolism, expression of CART seems to be different in the two strains. However, it should be taken into account that we analyzed expression of CART in the whole hypothalamus of B1B2KO mice, and not only in the lateral hypothalamic area, which may have contributed to the observed lack of differences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group found that CART mRNA expression is elevated in the lateral hypothalamic area of B1KO mice. 24 Even though B1KO and B1B2KO mice show similarities in some aspects of metabolism, expression of CART seems to be different in the two strains. However, it should be taken into account that we analyzed expression of CART in the whole hypothalamus of B1B2KO mice, and not only in the lateral hypothalamic area, which may have contributed to the observed lack of differences.…”
Section: Discussionmentioning
confidence: 99%